The effectiveness of using Delta Hedging strategies toward Malaysian Foreign Exchange market / Siti Nazrinah Aspar - Aspar, Siti Nazrinah (2017)
This study explores the effectiveness of delta hedging strategies toward Malaysian Foreign Exchange Market. Malaysian Foreign Exchange Markets actually were traded one of the options strategy which is the hedging strategies but there were no test had been conducting this delta hedging strategies toward the risk and return foreign exchange market in Malaysian country. The dummies method were developed which is Sharpe Ratio replaced the adjusted measurement, Treynor Ratio replaced volatility variance and Jensen Alpha replaced the level of volatility. By using the CAPM method to predicting the risk and return in Foreign Exchange Markets. There were three groups of asset classes which are equity group, fixed income group and balanced group. The methodology of this research paper will analysis one of the group of asset classes has the lowest risk and return toward the foreign exchange market itself.